Diagnosis and Treatment of Severely Malnourished Children in Outpatient Therapeutic Programme (Global Journal of Medical Research, 2023)
Severe acute malnutrition among children is still one of the main public health challenges in the 21st century particularly in developing countries It is associated with a high risk of morbidity and mortality The goals of management of SAM are to prevent short-term mortality achieve sustained nutritional recovery to reduce susceptibility to life-threatening infections and support neurocognitive development In addition to that SAM children need urgent lifesaving treatment to survive The outpatient therapeutic feeding program is one dimension of the community-based management of acute malnutrition that provides screening diagnostic and treatment services for uncomplicated SAM children 6 59 months of age by giving home-based treatment as Ready-to-use Therapeutic Food and routine medical treatment This review article gives a comprehensive update on outpatient therapeutic programmes in light of recently published standard treatment guidelines for the management of uncomplicated severe acute malnutrition
Keywords: severe acute malnutrition; outpatient therapeutic program; malnourished children